Trace metal sources and cycling in tropical oxygen minimum zones - Rapp, Insa (2018)
This thesis discusses sources and cycling of trace metals in tropical oxygen minimum zones. This thesis presents a new developed method for the analysis of a range of trace metals (iron, cadmium, nickel, zinc, copper, lead, cobalt and manganese) at trace levels in seawater. In the following chapters trace metal data from two distinct oxygen minimum zones are presented, one in the Eastern Tropical North Atlantic off the coast of Mauritania and one in the Eastern Tropical South Pacific off the coast of Peru. The work has a particular focus on the redox-sensitive trace metals, iron, cobalt and manganese and the influence of seawater oxygen concentrations on the sources and distribution of these trace metals. Finally differences in trace metal distributions between the two study regions are discussed.